Genocias ir rezistencija Nr. 10(2) - Lebedeva, Natalija; Stankeras, Petras; Bubnys, Arūnas; Zizas, Rimantas; Bagušauskas , Juozapas Romualdas; Jonušauskas, Laurynas; Anušauskas, Arvydas; Žilinskas, Justinas; Berenis, Vytautas; Jakubčionis, Algirdas; Bauža, Česlovas; Fabijonavičiūtė, Agnė (Genocidas ir rezistencija, 2001)
Pilnas leidinys (nuskenuota popierinė versija)